Advanced NXT The Da Vinci Inventions Book - Scholz, Matthias Paul (Apress : Imprint: Apress, 2007)
This amply illustrated book is about building some of Leonardo da Vinci's most famous inventions with LEGO's breathtaking robot technology, the LEGO MINDSTORMS NXT. In this book, you will revive such fascinating devices as the flying machine, the aerial screw, the revolving bridge, the double leaf spring catapult, and the armored car-five centuries after their creation by the great Renaissance engineer. Using some of the most advanced programming environments for the NXT, you will make robots that work, move, and respond the way Leonardo intended his original inventions to do 500 years ago. By engineering the LEGO models contained in this, book you will not only become acquainted with the MINDSTORMS NXT technology, but also with strategies to build advanced robots with NXT and to program them using different state-of-the-art NXT programming languages such as NXT-G, NXC, RobotC, pbLua, and leJOS NXJ. For all five robots, historical background information is provided. Detailed high-quality step-by-step building instructions, as well as an elaborate guide for each single program enable both the inexperienced LEGO user as well as the NXT aficionado to become acquainted with the art of producing marvelous NXT creations and make use of many sophisticated features of the NXT. This book will unleash the creative powers that slumber in everyone and combine them with the pure joy of playing. But beware: you might be surprised by the stupendous results this combination is apt to spawn.